Studio Anywhere 2 : hard light : a photographer's guide to shaping hard light - Fancher, Nick (Rocky Nook, 2017)
With behind-the-scenes photos, lighting diagrams, and Lightroom settings for many scenarios, this book offers candid, practical, and valuable lessons on how to create successful and fresh photographs armed with only minimal gear, a resourceful mind, and a creative spirit. --